Construction of wall / Mohamad Fakrul Mohd Sok - Mohd Sok, Mohamad Fakrul (Universiti Teknologi Mara, Perak, 2016)
The purposed of writing this report is to explain about wall which is wall has known structural element used to divide or enclose, and, in building construction, to form the periphery of a room or a building which is supported the weight of floors and roofs, but modern steel and reinforced concrete frames, as well as heavy timber and other skeletal structures, require exterior walls only for shelter and sometimes dispense with them on the ground floor to permit easier access. The report also containing the introduction of industrial training which is included the objectives and benefits of industrial training to students. One of the benefits is gain work experience and transferable skills. In introduction, the report is about company background which is about Ma Khalthum Enterprise. Ma Khalthum Enterprise was located at Kampung Gong Kepas Dalam, Besut Terengganu. Then, also included the organizations charts, vision, mission and objectives. Meanwhile, in chapter 1, it is about literature review of wall. Which is including definition of wall, function of wall, basic types of wall, wall system, basic wall structure and basic type of wall. Lastly in chapter 2, my case study is at Gong Nangka, Kampung Raja, Besut, which is project of. In this chapter, I will explain more about the wall structure that has been used to complete the building.